2011
DOI: 10.1002/hep.24307
|View full text |Cite
|
Sign up to set email alerts
|

Three ulcerative colitis susceptibility loci are associated with primary sclerosing cholangitis and indicate a role for IL2, REL , and CARD9

Abstract: Primary sclerosing cholangitis (PSC) is a chronic cholestatic liver disease characterized by inflammation and fibrosis of the bile ducts. Both environmental and genetic factors contribute to its pathogenesis. To further clarify its genetic background, we investigated susceptibility loci recently identified for ulcerative colitis (UC) in a large cohort of 1186PSC patients and 1748 controls. Single nucleotide polymorphisms (SNPs) tagging 13 UC susceptibility loci were initially genotyped in 854 PSC patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 50 publications
1
79
0
1
Order By: Relevance
“…[79][80][81][82] It is still unknown whether individual differences in PSC sub-phenotypes are driven by genetic background. The PSC Immunochip sub-phenotyping project, a study initiated by the International PSC study group (IPSCSG) is currently investigating, these possible associations between PSC risk loci and PSC sub-phenotype.…”
Section: Genetic Biomarkersmentioning
confidence: 99%
“…[79][80][81][82] It is still unknown whether individual differences in PSC sub-phenotypes are driven by genetic background. The PSC Immunochip sub-phenotyping project, a study initiated by the International PSC study group (IPSCSG) is currently investigating, these possible associations between PSC risk loci and PSC sub-phenotype.…”
Section: Genetic Biomarkersmentioning
confidence: 99%
“…Örneğin; "protein tyrosine phosphatase, non-receptor type (PTPN22)" genindeki R620W varyantı Tip 1 diyabet ve romatoid artrit için güçlü bir risk faktörü iken Crohn hastalığı için koruyucu etkiye sahiptir. 48 Bu ortak genlerin etkileri, bazen komplikasyon riskini belirlemeye de ışık tutabilir. "Macrophage stimulating 1 (MST1)", "interlökin 2 (IL2)", "caspase recruitment domain family, member 9 (CARD9)" ve "V-Rel avian reticuloendotheliosis viral oncogene homolog (REL)" genleri ülseratif kolit ve komplikasyonu olan primer sklerozan kolanjit ile ilişkilidir.…”
Section: İnflamatuar Barsak Hastaliklariunclassified
“…MST1 has been linked to IBD already before whereas BCL2L11 is known to be involved in apoptotic processes. Shortly afterwards, the same authors listed IL-2, CARD9 and REL, all involved in innate and adaptive immunity, linked to PSC [5]. The largest genetic study was reported recently [6].…”
Section: Primary Sclerosing Cholangitismentioning
confidence: 99%